ALTERNATIVE MARKETING STRATEGIES OF TRADITIONAL DRUG IN FACING THE NEW NORMAL ERA AS THE IMPACT OF COVID 19 - Yulia, Evi; Nurcholidah, Lilik; Sari, Kurnia Riska (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The purpose of this research is to find out alternative marketing strategies for traditional medicine in the face of the new normal era as the impact of the second covid 19 to find out the best alternative strategy that can be used for traditional medicine in facing the new normal era as the impact of covid 19. This type of research is qualitative with tools The analysis used is a SWOT analysis. The results of the study indicate that an alternative strategy that can be used is the SO Strategy, one of which is by conducting or increasing the marketing of herbal medicines by expanding the media. ST strategy, one of the strategies is to open outlets or branches elsewhere to avoid long queues due to the narrow business location. The WO strategy, one of the strategies is to make unique packaging to attract consumers, to provide delivery facilities. WT strategy. there needs to be training for employees so that they can make quality instant products such as instant turmeric herbs, instant ginger, instant temulawak and other herbs. The best alternative strategy is to make instant ready-to-eat traditional medicines with different variants, provide delivery facilities, make unique and attractive packaging so that consumers are more interested in traditional medicinal products. Finally, providing training to employees to be able to make quality instant products.